Assessment of non-disabled individuals walking with partial body weight support over ground and on treadmill - Barela, Ana Maria Forti (2015)
Background: Partial body weight support (BWS) systems have been used with treadmills as a strategy for rehabilitation of individuals with gait impairment. Considering that over ground is the commonly surface used for walking, it would be important to compare the use of a BWS system on treadmill and over ground. Aim: To analyze healthy adults walking with no harness and with 30% BWS on treadmill and over ground. Method: Kinematics data from 14 healthy adults (26 ± 3 years old) were acquired as they walked with 30% BWS and with no harness over ground and on treadmill. From these data, temporal-spatial walking parameters and joint and segmental angles were calculated. Results: Several parameter of walking over ground and on treadmill were different and the effects of partial BWS depended on the type of surface the participants walked. In general, walking over ground was characterized by faster and longer strides and with larger body segments excursion compared to walking on treadmill. Participants presented the most stable walking pattern as they walked over ground with BWS. Interpretation: Changes presented by healthy adults were towards an adjustable and adaptable pattern performed under a more stable and closer provided by over ground surface.